The Implementation of Presidential Instruction No. 1 of 2025 on Spending Efficiency in the Execution of the Fiscal Year 2025 Budget at the Legal Bureau of the Regional Secretariat of East Java Province - Wahyu Priandanata; Tauran T; Indah Prabawati; M Noer Falaq Al Amin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Presidential Instruction No. 1 of 2025 on Expenditure Efficiency in the Implementation of the State Budget (APBN) and Regional Budget (APBD) for Fiscal Year 2025 is a strategic policy that requires local governments to adjust non-priority expenditures without compromising the quality of public services. This study aims to analyze the implementation of this policy at the Legal Bureau of the East Java Provincial Secretariat. The approach used is descriptive qualitative, employing George Edward III’s policy implementation model, which encompasses communication, resources, disposition, and bureaucratic structure. Data were collected through interviews, observations, and documentation, and subsequently analyzed using an interactive model. The results of the study indicate that the implementation of the expenditure efficiency policy has generally been quite effective. Policy communication has been understood by implementers, although there are still limitations regarding technical clarity. From the resource perspective, budget cuts, particularly regarding official travel and support expenditures, have become the primary challenge, leading to limited mobility and the potential for reduced effectiveness, especially in handling litigation cases. Implementers’ dispositions demonstrate a strong commitment, while the bureaucratic structure continues to adhere to existing operational standards with technical adjustments; however, it lacks specific guidelines regarding efficiency. This study concludes that policy implementation has aligned with national policy directions; however, a gap persists between efficiency demands and operational needs.